2022
DOI: 10.3390/su142114550
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Constraints of Adopting New Cowpea Varieties in Three Agro-Ecological Zones in the Senegalese Peanut Basin

Abstract: Socio-economic constraints like gender, education, age, and income significantly affect the adoption of improved agricultural technologies. The objective of this study was to determine socio-economic factors that affect the adoption of improved cowpea varieties in the Senegalese peanut basin. The study was conducted in three (Bambey, Kebemer, and Kaffrine) of six regions of the peanut basin based on regional importance of cowpea production and rainfall gradient. In each study region, ten villages were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Field experiments were conducted near the National Center for Agronomic Research (CNRA) in Bambey, Senegal (14.709874°N and −16.481225 W, Figure 1). Crop production in the Bambey (Diourbel) region is generally rainfed and dominated by millet, cowpea, and groundnuts integrated with livestock farming or forestry (Beye et al., 2022). The climate is of the Sahelo–Sudanian type and is characterized by an average annual temperature of 27–28°C and annual rainfall amounts of 520 mm from 1991 to 2016 (Climate Research Unit of East Anglia, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Field experiments were conducted near the National Center for Agronomic Research (CNRA) in Bambey, Senegal (14.709874°N and −16.481225 W, Figure 1). Crop production in the Bambey (Diourbel) region is generally rainfed and dominated by millet, cowpea, and groundnuts integrated with livestock farming or forestry (Beye et al., 2022). The climate is of the Sahelo–Sudanian type and is characterized by an average annual temperature of 27–28°C and annual rainfall amounts of 520 mm from 1991 to 2016 (Climate Research Unit of East Anglia, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In Senegal, farming systems are dominated by cereal monoculture generally practiced in fields closer to farmsteads and cereals‐legumes rotations system in “bush fields” farther from the village (Beye et al., 2022; Samaké et al., 2006). Planting monoculture cereals in fields around the home allows generally good (average or more) yields because of large quantities of domestic organic wastes added to the soil (Tounkara, 2017) and used as an effective way to meet the growing demand for food (Franquesa, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the yield advantage of these new varieties, a recent study showed that majority of farmers (67%) in Senegal did not use improved cowpea varieties, and the main reasons were low seed availability (78.8%) and limited access to technical knowledge and information (76.3%), with only 5.8% indicating that seed price was a barrier to adoption (Beye et al, 2022). This suggests that new cowpea varieties are less known by producers and little information is available on best agronomic practices to improve grain and fodder yields of these varieties in the different environments in cowpea-producing regions (Beye et al, 2022;Dube & Fanadzo, 2013;Kristjanson et al, 2002). In Nigeria, research of Omokonye et al (2003) showed a significant variation in grain and fodder productivity among dual-purpose cowpea varieties, with more than 100% seed and fodder yield differences among tested dual-purpose cowpea varieties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its important nutritional potential, its short biological cycle makes this crop ideal for participation in organic farming systems due to its high rates of nitrogen fixation, phosphorus use efficiency and regrowth capacity [ 16 , 17 ]. Like other leguminous crops, it enhances soil improvement due to its ability to coexist with several Rhizobium bacteria species [ 18 , 19 ], resulting in the enrichment of the soil with nitrogen [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%